Annual Plan Programme 2001-2002 Volume-I Sector : Agriculture and Allied Activities Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2001)
Rice cultivation and its importance in these Islands cropping system has no room to doubt about. The agriculture in these Islands is more recent and out of the total area of flat land available, paddy shares 12,000 ha. alone and there exists a little scope for further expansion of area. This available 12,000 ha. is utilised for cultivation of paddy, pulses, oilseeds, vegetable etc. Rainfall is the only support of cropping in these Islands, so paddy is grown as rainfed crop and thus scope for raising a second crop of paddy is very much limited due to non-availability of any underground water source for irrigation Pulses, oilseeds, vegetables etc. are being grown in paddy fallows while tuber crops and sugarcane as mono-crops in limited scale.
Andaman and Nicobar Administration, Planning Department